Analysis Of Promotional Strategies In PT Sinar Sagara Sejahtera Sumedang - Putri, Anggi Septiani; Kurniasih, Nining; Gumilang, Risa Ratna (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2025)
PT Sinar Sagara Sejatera Sumedang is a company engaged in the fashion industry to produce special women's shoes and sandals. Every company certainly requires good marketing management to achieve optimal sales targets, especially regarding promotional strategies that can influence consumers. Therefore, this study aims to determine the analysis of promotional strategies at PT Sinar Sagara Sejahtera Sumedang as well as obstacles and solutions to its implementation. The method used is a qualitative method with informants totaling 10 people. Data collection techniques of this research through observation, interviews, documentation and triangulation. The results showed that the promotion strategy at PT Sinar Sagara Sejahtera was good enough by implementing personal selling and sales promotion optimally. However, the company has not been maximized in implementing advertising, public relations and direct marketing because it has not provided print media advertisements, has never participated in exhibitions/events and does not have its own website on telemarketing